2005
DOI: 10.1007/s10661-005-7056-5
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals: Inputs, sedimentation and accumulation in San Vicente Bay, Chile

Abstract: The present study deals with sediment dynamics affecting sediment-associated metal distributions in an embayment system experiencing pollution from coastal industries. Sedimentary metal content may originate from diagenetic processes of foundation rock on the bottom, allochthonous minerals from natural sources, and metals from industrial effluents along the coast. The study presents experimental estimations of quantities of metals entering the bay in industrial waste-water, measurements of metal content in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…(Ahumada 1992;Ahumada and Vargas 2005). According to these authors, in the NE zone of the bay sedimentation velocity and organic matter content are greater than in other zone of the bay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Ahumada 1992;Ahumada and Vargas 2005). According to these authors, in the NE zone of the bay sedimentation velocity and organic matter content are greater than in other zone of the bay.…”
Section: Resultsmentioning
confidence: 99%
“…Rudolph et al (2002) reported levels between 1.3 and 12.6% for sediments from the NE zone; Mudge and Seguel (1999) reported levels in the interval 6.5-23.3%; and Ahumada and Vargas (2005) between 0.3 and 0.8% for sediments from the south-central zone. The lower % TOC obtained in this study may be explained by the mitigating activities carried out in the area in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the roadside sediments were heavily polluted with heavy metals. Ahumada and Vargas, 2005, studied trace metal inputs, sedimentation and accumulation in San Vicente Bay, Chile and showed that the metals associated with particulate material from trap was Zn > Cr  Cu  Pb > Ni > Cd and the abundance of metals in sediments was Zn > Cr > Cu > Pb > Ni >Cd. Papadopoulos, et al, 1997, examined Cr, Cu, Fe, Ni, Pb and Zn in marine sediment and found the level of contamination very high.…”
Section: Instrumentation Methodsmentioning
confidence: 99%
“…Lead and cadmium contamination of bottom, lake and river sediments has been studied by many authors (Ahumada and Vargas, 2005;Ikem et al, 2003;Fytianos and Lourantou, 2004;Lima et al, 2001;Ho and Egashira, 2000). A long term monitoring of heavy metal concentration in sediments from drinking water reservoirs is important for an evaluation of the potential risks concerning drinking water quality.…”
Section: Introductionmentioning
confidence: 99%